Latent structure and convergent validity of a new authoritarianism scale - Mihić, Vladimir; Bodroža, Bojana; Čolović, Petar (Primenjena psihologija, 2009)
Two studies, aimed at the assessment of internal psychometric properties and construct validity of the new authoritarianism scale, UPA-S, are presented in the paper. The UPA-S scale contains 47 items originating from two earlier authoritarianism scales- ADO (regarding authoritarianism as a personality trait) and AUT-NS (considering authoritarianism as an attitude syndrome). The main aim of the Study 1 was the assessment of internal psychometric properties of the UPA-S scale. Applying the principal component analysis with Promax rotation, three latent dimensions were extracted and interpreted as authoritarian submissiveness, authoritarian aggressiveness and stoicism. The reliability, homogeneity and representativeness indices of the three resulting scales of the UPA-S were satisfactory. Convergent validity of the UPAS was examined in Study 2. By means of confirmatory factor analysis, three models (involving UPA-S scales, Altemeyer’s RWA, Revised F scale, Social Dominance Scale and Modern Racism Scale) were tested. The best- fitting model consisted of two correlated latent dimensions, the first one including authoritarianism scales, and the second one including the measures of related constructs. The results suggest that the psychometric properties of the UPA-S are satisfactory, and at the same time support the views which regard authoritarianism as a multi-dimensional construct which consists of both specific attitudes and personality characteristics.